2021
DOI: 10.3389/fpsyg.2020.615910
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Psychological Capital and Gender in University Students’ Entrepreneurial Intentions

Abstract: Universities increasingly play an important role in entrepreneurship, which has contributed to gender equality in the business world. The aim of this study is to establish a causal model of entrepreneurial intentions and explore it by gender, based on the dimensions of the Theory of Planned Behavior, and how these are mediated by the individuals’ resilience and psychological well-being. The previous work experience was considered as one of the control variables, in order to analyze whether this influence the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 96 publications
(104 reference statements)
4
30
0
Order By: Relevance
“…Our findings indicate that spirituality mediates the relationship between PBC and SEI, and between attitude toward a behavior and intentions to undertake in a social way in Portuguese students. The way in which spirituality influences the individual to have a behavior that creates a positive effect on society and his/her perceived ability to overcome obstacles, makes them more resilient and persevering ( Margaça et al, 2021 ). In addition, spirituality also empowers people to face the adversities of daily life, in a personal and unique way ( Benavent, 2014 ).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate that spirituality mediates the relationship between PBC and SEI, and between attitude toward a behavior and intentions to undertake in a social way in Portuguese students. The way in which spirituality influences the individual to have a behavior that creates a positive effect on society and his/her perceived ability to overcome obstacles, makes them more resilient and persevering ( Margaça et al, 2021 ). In addition, spirituality also empowers people to face the adversities of daily life, in a personal and unique way ( Benavent, 2014 ).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…As several studies on entrepreneurial intentions point out (e.g., Ward et al, 2019 ; Margaça et al, 2021 ), also when we study the intention to engage in SE, the individuals’ training/academic area is not limited to the area of management and business. Few studies have been done on the relationship between variables such as spirituality and its intrinsic values and SEI.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Psychological capital represents the development of positive psychology of people, resulting positive organizational behaviors and demonstrates performance (Costa and Neves, 2017); and it includes four dimensions: self-efficacy, hope, optimism, and resilience (Luthans et al, 2007a). Psychological capital is related to the achievements and well-being of individuals (Margaça et al, 2020), and it can be exploited like social resources (Luthans et al, 2006). Several studies have indicated that internet addiction is negatively correlated with psychological capital (Simsek and Sali, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, women have been found to be less ambitious and to have lower risk tolerance than men (Cardella et al, 2020). Similarly, (Margaça et al, 2020) found that female entrepreneurs possess a tendency toward taking less risk. Thus, entrepreneurial experience enhances female entrepreneurs' risk awareness, and they are more likely to engage in business planning activities to avoid uncertainty and decrease future risk (Brinckmann et al, 2010).…”
Section: Gender Differencesmentioning
confidence: 98%